Sexual reproduction of clonal dwarf shrubs in a forest-tundra ecotone - Manninen, Outi; Tolvanen, Anne (Springer, 2017)
Successful sexual reproduction may be more important for regeneration of clonal species in high-latitude and -altitude areas than has been previously suggested. We investigated the potential of Vaccinium myrtillus, V. vitis-idaea and Empetrum nigrum ssp. hermaphroditum (E. hermaphroditum) for sexual reproduction at three sites in the forest-tundra ecotone in Finnish Lapland. We studied whether the potential differs between plant communities, whether disturbance enhances germination, and whether seedling emergence is limited by seed availability. We established a field experiment with disturbance and sowing treatments, and monitored seed and seedling numbers and survival rates for two years. The number of mature seeds of V. myrtillus was higher in plants from the tundra heath than in those from the coniferous and mountain birch forests. The number of mature seeds and seedlings emerging from the seed bank of E. hermaphroditum tended also to be higher in the tundra heath. Disturbance marginally increased the seedling emergence of V. myrtillus and E. hermaphroditum, whereas sowing generally increased the seedling numbers. The seedling number of V. myrtillus was lower in the tundra heath and that of E. hermaphroditum was lower in the coniferous forest than at the other sites. Seedling survival was equal for all plant species at all sites. We conclude that the capacity for sexual reproduction varies among plant communities, and seed availability is a stronger constraint than microsite availability for the studied species. Once the crucial early phase of seedling establishment is overcome, seedling survival enables successful recruitment of V. myrtillus, V. vitis-idaea and E. hermaphroditum in the subarctic area.
Keywords: Vaccinium myrtillus; Vaccinium vitis-idaea; Empetrum nigrum; lisääntyminen; taimet; reproduction; seedlings